The ileocecal valve in transabdominal ultrasound. Part 2: Pathological lesions - Smereczyński Andrzej; Goncerz Grzegorz; Kołaczyk Katarzyna (Journal of Ultrasonography)
The aim of this paper is to present our experience in transabdominal ultrasonography of ileocecal valve lesions. The ileocecal valve, located in the central part of the ileocecal bowel segment, is rarely the primary site of disease processes. It is usually involved by pathologies in adjacent bowel segments. These are primarily infectious diseases such as yersiniosis, campylobacteriosis and salmonellosis. Typical location of Crohn’s lesions also promotes valve involvement. The appearance of the lesions in these cases is characterized by a symmetrical submucosal thickening of the bowel involved over a longer segment. Non-malignant valvular hyperplasia is relatively commonly identified as lipomatosis, manifested by symmetrical enlargement and smooth outlines. However, valvular lipoma causing an asymmetrical hyperechoic bulge is a rare finding. ileocecal valve lipomatosis or lipoma should not be misdiagnosed as a lipoma of the cecoascending part of the colon and, the other way round, a right colonic lipoma should not be mistaken for a fatty valve. Polyps on the ileocecal valve, although sometimes detected, were not identified in our material. Adenocarcinoma, which is found in the cecum in approximately ¼ of cases, is the most common malignancy, followed by neuroendocrine tumor and, rarely, lymphoma. In three cases of malignant involvement of the ileocecal valve, we observed irregular hypoechoic thickening with complete loss of wall stratification, with the lesions causing symptoms of small bowel obstruction in two of these cases. The nearly forgotten ileocecal valve syndrome, also known as Bauhin’s ileocecal valve syndrome, characterized by intermittent right iliac fossa pain, is also briefly discussed. Transabdominal ultrasound can be used as an initial diagnostic tool in some of these pathologies.